Exposure to a maternal cafeteria diet changes open-field behaviour in the developing offspring - Speight, Abigail; Davey, William; McKenna, Emily; Voigt, Jörg-Peter (Elsevier, 2017)
The early postnatal period is a sensitive period in rodents as behavioural systems are developing and maturing during this time. However, little is currently known about the behavioural effects of feeding a hyper-energetic cafeteria diet (CD) during the lactational period when offspring behaviour is tested during early adolescence. To this end, 23 days old offspring from dams (Wistar) fed on CD during lactation were tested in either the open-field or the elevated plus-maze for exploration and anxiety-related behaviour. On postnatal day 9, maternal behaviour and non-maternal behaviour of the dam was assessed. It was hypothesized that lactational CD feeding would reduce anxiety in the offspring. CD-fed dams had a higher energy intake, due to an overconsumption of sugars and fats. When offspring from these dams were exposed to the open field after weaning, their locomotor activity was increased. They entered the more aversive inner zone of the open-field after a shorter latency, made more entries into and spent more time in the inner zone. Anxiety-related behaviour was not affected upon exposure to the elevated plus maze, suggesting anxiolysis in the open-field only. Increased maternal licking/grooming behaviour could possibly contribute to the anxiolytic phenotype as observed in the offspring from the CD group. In conclusion, we demonstrate that lactational overfeeding impacts on the development of behaviour in the early adolescent rat.